Bench-to-bedside review: Toll-like receptors and their role in septic shock - Opal, Steven M (BioMed Central, 2002)
The Toll-like receptors (TLRs) are essential transmembrane signaling receptors of the innate immune system that alert the host to the presence of a microbial invader. The recent discovery of the TLRs has rapidly expanded our knowledge of molecular events that initiate host–pathogen interactions. These functional attributes of the cellular receptors provide insights into the nature of pattern recognition receptors that activate the human antimicrobial defense systems. The fundamental significance of the TLRs in the generation of systemic inflammation and the pathogenesis of septic shock is reviewed. The potential clinical implications of therapeutic modulation of these recently characterized receptors of innate immunity are also discussed.